Study on Dr. Ambedkar as a Emancipator of the Dalits: Unveiling the Multi-Faceted Role of Dr. Ambedkar in Modern India (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Dr. Ambedkar was an opportunity warrior of the most genuine kind, not simply longing for setting India compel from British standard, yet of changing India into a nation where opportunity holds importance for everybody. He devoted his life for inspiring of the Dalits. Ambedkar wished social reformers to make general supposition to battle the gross inequalities in the general public. It is extremely tragic that the media in the past and additionally the present has anticipated Ambedkar chiefly as a severe pundit of the Hindu religion and an extraordinary social renegade. They have disregarded Dr. Ambedkar's multi-faceted identity. Here is our little exertion to center his job in Modern India.